The Development of Learning Media Novelmatika e-Book to Improve Statistics Concepts Understanding: The Development of Learning Media Novelmatika e-Book to Improve Statistics Concepts Understanding - Yenni Dian Anggraini (Persatuan Guru Republik Indonesia Provinsi sulawesi Tenggara, 2020)
The use of instructional media is expected to help students learn mathematical concepts in a meaningful way, which can link concepts in mathematics and apply them in solving problems of daily life. The learning media used must discuss mathematics contextually. It means in accordance with the problems that exist in students' daily lives. Therefore this study aims to develop learning media with e-book models of Novelmatika on statistical material. The use of the term Novelmatika is intended so that when students read this e-book it is like reading a novel that is fun and not burdened like reading a textbook. This research is a development research. The design of this study uses the ADDIE (Analysis-Design-Development-Implementation-Evaluation) model. This research has been carried out to the Evaluation stage, namely by conducting pretest-posttest before and after the use of the Novelmatika e-book. The mean pretest value was 52.30%, while the average posttest value was 79.46%. This means an increase in understanding of statistical concepts in students by 27.16%.